Was There a Universal Homicide Increase in 2014 to 2016 and 2019 to 2020? - Rogers, Meghan L. (Journal of contemporary criminal justice, 2024)
This article explores whether there was a universal increase in homicide victimization in 2014 to 2016 and 2019 to 2020. Although the United States observed increases in homicide victimization in 2014 to 2016 and 2019 to 2002, it is unlikely that all nations observed simultaneous increases in homicide victimization. Therefore, we explore whether countries observed increases in homicide victimization from 2014 to 2016, only part of the time, and before and after 2014 to 2016. We also investigated which nations observed an increase in homicide victimization from 2019 to 2020. We used WHO mortality homicide victimization data for an initial sample of 116 nations. In general, it does not appear that there was a simultaneous universal increase in the times under study. However, most of the sample at some point between 2014 and 2016 experienced increases in homicide victimization.